ANALISIS KEMAMPUAN PEMECAHAN MASALAH DITINJAU DARI COGNITIVE LOAD THEORY PADA MODEL PEMBELAJARAN PBL DENGAN PENDEKATAN REALISTIK - Pingkan Harbinawanti; Budi Waluya; Tri Sri Noor Asih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to determine the quality of problem solving abilities in terms of cognitive load theory in the PBL learning model with a realistic approach. The research design used a one-shot case study of 2 classes, namely the experimental and control classes at Dr. Vocational School. Tipto Semarang. Data collection techniques in research use test, questionnaire, observation, interview and documentation methods. The research results show that Hypothesis 1 shows that the average test results are tcount = 1.871 and ttable = 1.697. So it can be concluded that tcount > ttable, then H0 is rejected, meaning that the average problem-solving ability in terms of cognitive load theory in the PBL learning model with a realistic approach is more than the minimum criterion (70). Hypothesis 2 results of the classical completeness test obtained Zcount = 2.79 and Ztable = 1.64 because Zcount > Ztable then H0 is rejected so it can be concluded that the proportion of problem solving ability in terms of cognitive load theory in the PBL learning model with a realistic approach exceeds 75%. Hypothesis 3: The results of the average difference test calculation show that tcount = 6.483 and ttable = 1.697 because tcount > ttable, so H0 is rejected. So it can be concluded that the average problem-solving ability in terms of cognitive load theory in the PBL learning model with a realistic approach to the experimental class is more than the average problem-solving ability of the control class. Hypothesis 4 is the quality of problem solving abilities in terms of cognitive load theory in the PBL model with an effective realistic approach to increase the results of students' problem solving abilities and based on the results of the analysis of the N-Gain hypothesis test in the medium category which is equal to 0.38293 or if it is rounded up to 0.38 and is included in the medium category.